2013
DOI: 10.1212/wnl.0b013e31829d8714
|View full text |Cite
|
Sign up to set email alerts
|

Meningioangiomatosis

Abstract: A 58-year-old man presented with a 6-month history of headaches, progressive left homonymous hemianopia, and right-sided paresthesias. MRI revealed bilateral parietal and occipital enhancing lesions (figure 1, A-C) suggestive of cerebritis or posterior reversible encephalopathy syndrome due to history of hypertension. Worsening vision prompted neuroimaging 18 months later, showing contrast-enhancing cortical lesions in the posterior frontal region; fluid-attenuated inversion recovery abnormalities in the white… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…The limited number of MA-M cases may account for such a difference. MA usually presents with a male predisposition [69], consistent with the literature [4], and male predominance was more obvious in MA-M (unlike conventional meningioma) than in pure MA. This finding suggests that hormones may play an important role in the pathogenesis of MA-M. Wiebe et al suggested that the temporal lobe was the most frequently involved in MA [1], while the frontal lobe seemed to be more affected, based on our analysis.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The limited number of MA-M cases may account for such a difference. MA usually presents with a male predisposition [69], consistent with the literature [4], and male predominance was more obvious in MA-M (unlike conventional meningioma) than in pure MA. This finding suggests that hormones may play an important role in the pathogenesis of MA-M. Wiebe et al suggested that the temporal lobe was the most frequently involved in MA [1], while the frontal lobe seemed to be more affected, based on our analysis.…”
Section: Discussionsupporting
confidence: 83%
“…Pure MA can even present as meningioma-like dural attachment and homogeneous contrast enhancement [21,28]. In a few reported cases [1,17,32,45,69,73,80], including case 8 and case 9 in our series, pure MA has exhibited a unique presentation of gyriform alteration or gyriform enhancement (Fig. 1).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…2 Bilateral occipital cortical involvement with associated progressive cortical blindness, similar to our case, has been reported only once previously. 5 The only known treatment for meningioangiomatosis is surgical resection; however, in this unique case, surgical resection was not feasible because of the extensive, diffuse nature of the disease. 2 Since one of the primary histopathologic features of meningioangiomatosis is meningovascular proliferation, we hypothesized that antiangiogenic therapy, such as bevacizumab, a recombinant humanized monoclonal antibody that blocks angiogenesis by inhibiting vascular endothelial growth factor A, might be beneficial.…”
Section: 2mentioning
confidence: 89%
“…4 Sporadic cases are typically solitary and symptomatic, while NF2-associated meningioangiomatosis is often multifocal and asymptomatic. 5 The primary histopathologic features are leptomeningeal and perivascular mesenchymal cell proliferation and the presence of dysplastic neurons. Immunohistochemistry is of limited diagnostic value.…”
Section: 2mentioning
confidence: 99%